Psychosocial interventions for autistic children and adolescents delivered by non-specialists in low- and middle-income countries: a scoping review - Cherewick, Megan; Daniel, Christina; Shrestha, Catherine Canavan; Giri, Priscilla; Dukpa, Choden; Cruz, Christina M.; Rai, Roshan P.; Matergia, Michael (Frontiers in Psychology, 2023)
Background. Most autistic individuals reside in low-and middle-income countries (LMIC) and have limited access to medical providers and specialists. Support for delivery of psychosocial interventions by non-specialists is growing to address this mental health care gap. This scoping review involved a systematic analysis of studies of non-specialist delivered psychosocial interventions for children and adolescents diagnosed with autism and living in low-and middleincome countries. Methods. The primary objective of this review was to identify psychosocial interventions for autistic children and adolescents in LMIC delivered by non-specialists (parent, teacher, peer, community, multi-level) and to summarize resulting effects on targeted outcomes. The search strategy was completed in four databases with predetermined inclusion and exclusion criteria. The systematic search generated 3601 articles. A total of 18 studies met inclusion/exclusion criteria. Data extraction was completed, and results summarized by; 1) participant sample; 2) intervention procedures; 3) implementation by non-specialists; 4) effect on evaluated outcomes; and 5) assessment of risk of bias. Studies examined a range of child and adolescent outcomes including assessment of communication skills, social skills, motor skills, functional and adaptive behaviors, emotional regulation, attention and engagement, sensory challenges, depression, anxiety, and quality of life. Several studies also evaluated intervention effects on family relationships, parent/caregiver stress and parent/caregiver mental health. Results. Collectively, the 18 studies included a total of 952 ASC participants ranging in age from 2-16 years. Of the included studies, 8 studies were parent/caregiver-mediated, 1 study was peer-mediated, 2 studies were teacher-mediated, and 7 studies included multi-level non-specialist mediated components. Effects on evaluated outcomes are reported. Conclusion. Non-specialist delivered interventions for autistic children and adolescents are effective for an array of outcomes and are particularly well suited for low-and middle-income countries. Implications for future research are discussed.